FISIBILITAS VIRTUAL REALITY EXPOSURE THERAPY (VRET) UNTUK MENURUNKAN INTERACTION ANXIETY - Rini Liana Dewi; Tutty I Sodjakusumah; Aulia Iskandarsyah (Jurnal EMPATI, 2026)
Adolescence is a period of development in which individuals experience the highest levels of social anxiety. Interaction anxiety is a concern that arises in contingent interactions, including shyness, dating anxiety, heterosexual-social anxiety, and interpersonal anxiety. One effective therapy for reducing anxiety is exposure therapy. Recent research suggests the use of Virtual Reality Exposure Therapy (VRET), which involves exposing an individual to a computer-generated virtual environment based on the principles of exposure therapy and interaction anxiety theory. The purpose of this study is to develop a Virtual Reality Exposure Therapy (VRET) design to reduce interaction anxiety that is acceptable to high school students with interaction anxiety. Virtual Reality Exposure Therapy (VRET) consists of relaxation, practice, and levels 1 to 6. The research design used in this study is research and development. The study population consists of high school students in Bandung who experience interaction anxiety, and subjects were selected using purposive sampling. This study was conducted on 11 high school students aged 15-18 years who experienced interaction anxiety. The method used was an exploratory study. Data processing was performed using descriptive analysis. The results of this study indicate that the Virtual Reality Exposure Therapy (VRET) intervention design is feasible for application to high school students who experience interaction anxiety and has the potential to reduce interaction anxiety.